Student anxiety in the wake of the COVID-19 pandemic - Ulviyya Zulfiqarova; Birgitta Dresp-Langley (Academia Mental Health & Well-Being)
Meta-analyses of the pertaining literature have shown that generalized anxiety disorder (GAD) in youth particularly students is a prevalent syndrome in mental health issues identified in 2022, in the wake of the COVID-19 pandemic, by the World Health Organization and other national organizations such as Santé Publique France. This study, performed between 2022 and 2023, offers a pinhole view of student anxiety in the post-COVID-19 context at a French University. A sample population of 80 undergraduate medical students within the age range from 18 to 24 years was tested for GAD in a survey using an online version of the Hamilton Anxiety Scale (HAM-A). The total test scores indicate a prevalence of severe to very severe GAD in 36% of the sample population, which is consistent with results from studies on larger student populations in other countries. Further statistical analyses reveal a significantly higher number of psychological symptoms by comparison with somatic symptoms of GAD. The reasons why, under the light of the findings placed in the current societal context, student anxiety needs to be addressed in terms of a larger societal problem beyond the immediate consequences of the COVID-19 pandemic are discussed.